A new wild emmer wheat panel allows to map new loci associated with resistance to stem rust at seedling stage - Mastrangelo, Anna Maria; Roncallo, Pablo; Matny, Oadi; Čegan, Radim; Steffenson, Brian; Echenique, Viviana; Šafář, Jan; Battaglia, Raffaella; Barabaschi, Delfina; Cattivelli, Luigi; Özkan, Hakan; Mazzucotelli, Elisabetta (The plant genome, 2025)
Wheat stem rust, caused by Puccinia graminis f. sp. tritici (Pgt), is a major wheat disease worldwide. A collection of 283 wild emmer wheat [Triticum turgidum L. subsp. dicoccoides (Körn. ex Asch. & Graebn.) Thell] accessions, representative of the entire Fertile Crescent region where wild emmer naturally occurs, was assembled, genotyped, and characterized for population structure, genetic diversity, and rate of linkage disequilibrium (LD) decay. Then, the collection was employed for mapping Pgt resistance genes, as a proof of concept of the effectiveness of genome-wide association studies in wild emmer. The collection was evaluated in controlled conditions for reaction to six common Pgt pathotypes (TPMKC, TTTTF, JRCQC, TRTTF, TTKSK/Ug99, and TKTTF). Most resistant accessions originated from the Southern Levant wild emmer lineage, with some showing a resistance reaction toward three to six tested races. Association analysis was conducted considering a 12K polymorphic single-nucleotide polymorphisms dataset, kinship relatedness between accessions, and population structure. Eleven significant marker-trait associations (MTA) were identified across the genome, which explained from 17% to up to 49% of phenotypic variance with an average 1.5 additive effect (based on the 1-9 scoring scale). The identified loci were either effective against single or multiple races. Some MTAs colocalized with known Pgt resistance genes, while others represent novel resistance loci useful for durum and bread wheat prebreeding. Candidate genes with an annotated function related to plant response to pathogens were identified at the regions linked to the resistance and defined according to the estimated small LD (about 126 kb), as typical of wild species.
Keywords: Chromosome Mapping; Seedlings; Puccinia; Polymorphism, Single Nucleotide; nemoci rostlin; Linkage Disequilibrium; Disease Resistance; Plant Diseases; pšenice; Triticum; vazebná nerovnováha; odolnost vůči nemocem; mapování chromozomů; semenáček; Basidiomycota; jednonukleotidový polymorfismus; Genome-Wide Association Study; celogenomová asociační studie